Systematic Literature Riview dengan Metode Prisma: Modul Ajar Biologi dalam Kurikulum Merdeka: Penelitian - Ade Yulia; S. Syamsyurizal (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Merdeka Curriculum gives schools and teachers the freedom to adjust the curriculum to current developments. Given the importance of the role of teaching modules, the modules must be compiled completely, systematically, and operationally in accordance with the Merdeka Curriculum. This study aims to review several literature studies related to the implementation of Biology teaching modules in the Merdeka Curriculum. This research method uses PRISMA through the Publish or Perish software version 8 as a medium for collecting data and information relevant to the writing of this journal. The findings indicate that the characteristics and suitability of the implementation of teaching modules are in accordance with the principles of the Merdeka Curriculum and there are several obstacles or challenges in the implementation of biology teaching modules, one of which is the lack of teacher training and understanding of the concept and technical preparation of teaching modules.